2018
DOI: 10.1016/j.resuscitation.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Chest compression rates and pediatric in-hospital cardiac arrest survival outcomes

Abstract: Non-compliance with compression rate Guidelines was common in this multicenter cohort. Among ICU patients, slightly lower rates were associated with improved outcomes compared to Guidelines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 42 publications
(61 reference statements)
1
31
0
4
Order By: Relevance
“…Many studies have shown that chest compressions are often poorly performed [4,16]. The present data show that the compressions applied in the first group with no-sensor CPR were too fast; this has previously been associated with poorer survival [17,18]. Use of the feedback sensor improved the compression rate, with further improvement when real-time feedback was activated.…”
Section: Compression Frequencymentioning
confidence: 50%
“…Many studies have shown that chest compressions are often poorly performed [4,16]. The present data show that the compressions applied in the first group with no-sensor CPR were too fast; this has previously been associated with poorer survival [17,18]. Use of the feedback sensor improved the compression rate, with further improvement when real-time feedback was activated.…”
Section: Compression Frequencymentioning
confidence: 50%
“…Guimier hypothesized that the high energy needs of cardiac myocytes may preclude return of spontaneous circulation (ROSC) despite early and optimal resuscitation in patients with pathologic PPA2 variants, potentially because of an inability of the mitochondria to meet the energy demands of the cell (Guimier et al 2016). This theory may be especially applicable to our patient as the majority of pediatric patients with in-hospital cardiac arrests do achieve ROSC (Sutton et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…If spontaneous circulation is recovered, it is not uncommon for a child to have another CPA shortly afterwards and this second episode may be owing to PEA or an abnormal cardiac rhythm requiring defibrillation [12,13]. In many low-income settings without a cardiac monitor, the rhythm may not be known.…”
Section: Delivery Of Cardiopulmonary Resuscitationmentioning
confidence: 99%